0305 Irregularities in Sleep Duration and Biomarkers of Cardiovascular Disease across the Menstrual Cycle. (25th May 2022) - Dunietz, Galit; Shedden, Kerby; Michels, Kara; Chervin, Ronald; Lyu, Xiru; Freeman, Joshua; Baylin, Ana; O'Brien, Louise; Wactawski-Wende, Jean; Schisterman, Enrique; Mumford, Sunni
Abstract: Introduction: Irregular sleep duration may disrupt circadian rhythms necessary for optimal cardiovascular function. Yet, few studies have examined irregular sleep duration in relation to cardiovascular health, particularly among diverse cohorts of reproductive-age women. This study examined associations between sleep duration irregularities across the menstrual cycle and cardiovascular disease biomarkers in a cohort of healthy, premenopausal women. Methods: We utilized the BioCycle micro-longitudinal cohort study of 259 regularly menstruating women aged 18–44 years. This measurement-intense study collected cardiovascular disease biomarkers at key reproductive time-points along the menstrual cycle (approximately days 2, 7, 12, 13, 14, 18, 22, 27 of a 28-day cycle) across two cycles. Specifically, we assessed serum high-density lipoprotein (HDL), low-density lipoprotein (LDL), total cholesterol, triglycerides, and C-reactive protein (CRP). Women recorded sleep duration in daily diaries concurrently. We computed a system of four mathematical measures, the L-moments, robust versions of location, dispersion, skewness, and kurtosis for series of recorded sleep durations. Using linear mixed models with random intercepts and inverse probability weighting we estimated associations between irregular sleep duration and cardiovascular disease biomarkers in all women and within a subset of non-white women. Adjusted analysis accounted for baseline characteristics and time-varying hormonal changes across the menstrual cycle. Results: Woman-specific mean sleep duration ranged from 4.4 to 10.6 hours. A one-hour increase in dispersion of sleep duration was associated with a lower mean LDL and higher mean HDL for non-white women (-19.4%, 95%CI -30.9, -6.0% and 24.7%, 95%CI 8.2, 43.0, respectively). Unbalanced (skewed) sleep duration, frequent short or long hours, was associated with higher mean CRP for all women and non-white women (99.3%, 95%CI 17.2, 238.9 and 126.7%, 95%CI 3.1, 398.2, respectively), but lower total cholesterol (-10.9%, 95%CI -19.9, -1.0). Finally, irregular sleep durations, extreme short and long sleep bouts (kurtosis), were associated with reduced mean HDL for all women, and non-white women (-17.1%, 95%CI -31.1, -0.2 and -25.4%, 95%CI -39.5, -8.0, respectively). Conclusion: This micro-longitudinal study of premenopausal women found associations between irregularities in sleep duration and differences in CRP, LDL, HDL and total cholesterol, but not with triglycerides. These data suggest that even in young and healthy women, irregularities in sleep duration could have a potential impact on cardiometabolic health. Support (If Any): Dr. Dunietz was supported by a Mentored Research Scientist Development Award from the National Heart, Lung, and Blood Institute (K01 HL144914). This work was supported in part by the Intramural Research Program of the NIH, Eunice Kennedy Shriver National Institute of Child Health and Human Development (authors KAM, JRF, EFS, SLM; The BioCycle Study was funded under the following intramural contracts: HHSN275200403394C HHSN275201100002I, and Task 1 HHSN27500001).